Machine learning models for predicting return to sports after anterior cruciate ligament reconstruction: Physical performance in early rehabilitation - Ui-jae Hwang; Jin-seong Kim; Keong-yoon Kim; Kyu-sung Chung (Digital Health)
Objective Return to sports (RTS) after anterior cruciate ligament reconstruction (ACLR) is a crucial surgical success measure. In this study, we aimed to identify the best-performing machine learning models for predicting RTS at 12 months post-ACLR, based on physical performance variables at 3 months post-ACLR. Methods This case-control study included 102 patients who had undergone ACLR. The physical performance variables measured 3 months post-ACLR included the Biodex balance system, Y-balance test, and isokinetic muscle strength test. The RTS outcomes measured at 12 months post-ACLR included the single-leg hop test, single-leg vertical jump test, and Tegner activity score. Six machine learning algorithms were trained and validated using these data. Results Random forest models in the test set best predicted the RTS success based on the single-leg hop test (area under the curve [AUC], 0.952) and Tegner activity score (AUC, 0.949). Gradient boosting models in the test set best predicted the RTS based on the single-leg vertical jump test (AUC, 0.868). Conclusion Modifiable factors should be considered in the early rehabilitation stage after ACLR to enhance the possibility of a successful RTS.